Necropolitics and Gore Capitalism in the Colombian South Pacific Region - Pazos-Cárdenas, Mateo (Sociedad y Economía, 2021)
This article is aimed at analyzing certain aspects of the current situation in the Colombian South Pacific based on concepts of “necropolitics” (coined by the Cameroonian intellectual Achille Mbembe) and “gore capitalism” (developed by the Mexican philosopher Sayak Valencia). The method used to collect the information analyzed consisted of ethnographic field work over five months in seven municipalities located in the department of Nariño, in the Colombian South Pacific region. The theoretical developments by these two authors make it possible to analyze the current forms of violence in this region and how they impact the daily lives of the residents.